021 Therapeutic effects of MitoQ10 on hypertension and cardiac hypertrophy. (22nd September 2015) - McLachlan, J; Hamilton, C A; Beattie, E; Murphy, M P; Dominiczak, A F; Nicklin, S A; Graham, D
Abstract : Aim: There is increasing evidence that mitochondrial-generated reactive oxygen species contribute to the development of cardiovascular disease. We have previously demonstrated that administration of a novel mitochondrial-targeted antioxidant MitoQ10 protects against endothelial dysfunction, the development of hypertension and cardiac hypertrophy in stroke-prone spontaneously hypertensive rats (SHRSP). Here we investigated the therapeutic benefit of MitoQ10 during development of hypertension in combination with losartan. Additionally, we studied the direct effects of MitoQ10 on cardiomyocyte hypertrophy in vitro to determine the contribution of mitochondrial oxidative stress. Methods: Eight-week-old male SHRSP (n=5 to 7) were treated with low dose losartan (2.5 mg/kg/day); MitoQ10 (500 μmol/l); a combination of MitoQ10 and Losartan (M+L) or untreated for 9 weeks. Blood pressure was measured by tail cuff plethysmography and radiotelemetry. Aorta and mesenteric resistance arteries were isolated for assessment of endothelial function and structure. Cardiac mass and left ventricular mass indices were calculated. Mitochondria were isolated from hearts for mitochondrial superoxide production (EPR) and membrane potential measurements (JC-1). To study direct effects of MitoQ10 on cardiomyocyte hypertrophy, a rat cardiomyocyte cell line (H9C2) was pre-treated with 500 nM, 1 μM and 2 μM MitoQ10 before angiotensin II stimulation (100 nM). Cell size was measured at 96 h using ImageProPlus and cell viability was assessed by MTT assay. Results: Systolic blood pressure (p=0.001) and pulse pressure (p=0.019) were significantly lower in the M+L group compared to untreated SHRSP and demonstrated a greater improvement than MitoQ10 or low dose losartan alone. Cardiac hypertrophy was also significantly reduced in the M+L group (p<0.01). Basal nitric oxide bioavailability was significantly increased in aortas of the M+L treated group (p<0.05) compared to control. Pressure myography of mesenteric resistance arteries revealed a significant improvement in the media to lumen ratio (p<0.05). There were no differences in cardiac mitochondrial superoxide production and membrane potential. In H9C2 cardiomyocytes, MitoQ10 significantly inhibited angiotensin II-mediated hypertrophy (p<0.001). Conclusion: The combination of MitoQ10 and losartan protects against the development of hypertension, reduces cardiac hypertrophy and improves endothelial function in an additive manner. In vitro studies confirm the direct anti-hypertrophic effect of MitoQ10 in rat cardiomyocytes. MitoQ10 provides a novel approach to investigate the role of mitochondrial-specific oxidative damage and has potential as a new therapeutic agent in cardiovascular disease.